2022
DOI: 10.3389/fcimb.2022.1031463
|View full text |Cite
|
Sign up to set email alerts
|

Myosin-II proteins are involved in the growth, morphogenesis, and virulence of the human pathogenic fungus Mucor circinelloides

Abstract: Mucormycosis is an emerging lethal invasive fungal infection. The infection caused by fungi belonging to the order Mucorales has been reported recently as one of the most common fungal infections among COVID-19 patients. The lack of understanding of pathogens, particularly at the molecular level, is one of the reasons for the difficulties in the management of the infection. Myosin is a diverse superfamily of actin-based motor proteins that have various cellular roles. Four families of myosin motors have been f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 99 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…The same group recently demonstrated that myosin II plays an important role in growth, sporulation and hyphal development in Mucor. Interestingly, only disruption of one myosin II gene, mcmyo2A , led to abrogation of pathogenicity, while mcmyo2B deletion had no impact on virulence, although the mutant was similarly attenuated in growth ( Trieu et al., 2022 ). Iron acquisition is crucial for pathogenicity also in Mucorales, as M. lusitanicus that is not able to produce rhizoferrin, the mucormycete siderophore, was shown to be avirulent.…”
Section: Invertebrate Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same group recently demonstrated that myosin II plays an important role in growth, sporulation and hyphal development in Mucor. Interestingly, only disruption of one myosin II gene, mcmyo2A , led to abrogation of pathogenicity, while mcmyo2B deletion had no impact on virulence, although the mutant was similarly attenuated in growth ( Trieu et al., 2022 ). Iron acquisition is crucial for pathogenicity also in Mucorales, as M. lusitanicus that is not able to produce rhizoferrin, the mucormycete siderophore, was shown to be avirulent.…”
Section: Invertebrate Modelsmentioning
confidence: 99%
“…Therefore, this review will focus on alternative model systems that have been exploited so far for mucormycosis studies, highlighting novel alternative model animals or adapted methods established in the last three to four years to avoid repetition of what has already been reviewed in detail by Jacobsen (2019) . The alternative animal models presented in the review have significantly contributed to fostering our understanding of previously undescribed virulence factors of Mucorales, some of which are unique to this group of fungi ( Patiño-Medina et al., 2018 ; Patiño-Medina et al., 2019a ; Wurster et al., 2020 ; Alejandre-Castañeda et al., 2022 ; Itabangi et al., 2022 ; Trieu et al., 2022 ; Szebenyi et al., 2023 ). Moreover, these models have unveiled pathogen recognition and immune evasion strategies of Mucoralean fungi that are relevant for interactions with the human host ( Chamilos et al., 2008a ; Hoffmann et al., 2013 ; Inglesfield et al., 2018 ; López-Muñoz et al., 2018 ; Hassan et al., 2021 ; Itabangi et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…For experiments requiring drug treatment, dosage is determined by measuring the hemolymph volume of larvae of various weights and calculating the mean hemolymph volume/kg weight by linear regression [90]. The sporangiospore inoculum (usually 10 6 spores), any drugs being tested, and vehicles serving as infection or treatment controls, are injected diluted in 5-20 µL of insect physiological saline into the larval hemocoel via a hind pro-leg [89][90][91]. Infected larvae are incubated in the dark at 30 • C and monitored daily for survival.…”
Section: Galleria Mellonellamentioning
confidence: 99%
“…This fungus is also one of the agents that cause mucormycosis. Our study analyzes the structures and functions of some genes and gene families involved in controlling the filamentous phenotype and pathogenicity of this fungus, such as the gene families encoding myosin II and myosin V (Trieu et al, 2017(Trieu et al, , 2022. These studies showed that the virulence of M. lusitanicus is closely related to some of its phenotypic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed that the virulence of M. lusitanicus is closely related to some of its phenotypic characteristics. Specifically, growth rate, spore production, and yeast-like growth are signs that reduce the virulence of the fungus (Trieu et al, 2017(Trieu et al, , 2022.…”
Section: Introductionmentioning
confidence: 99%